Paparan Pornografi melalui Televisi dan Perilaku Seksual Remaja di SMA Negeri 2 Kendari - Yustiari Yustiari; Syahrianti Syahrianti (Health Information : Jurnal Penelitian, 2018)
The use of technology nowadays increasingly facilitates communication without being limited by space and time. At present print and electronic media is an environment that is close to teenagers. Television is an electronic media that is easily accessible to teenagers because of the large amount of information and news broadcast. This study aimed asses the exposure of pornography content through television and adolescents sexual behavior of SMAN 2 Kendari. The research designed to cross sectional study. The samples were 69 adolescents of SMAN 2 Kendari. There were 36 respondents (53.1%) had low exposure to pornography content from the television. Almost all respondents (86.96%) had mild sexual behavior. The majority of sexual behavior characteristics were holding hands (57.9%), and kisses involving the tongue during dating. Most respondents' peer had low behavior (57.9%).